The Impact of Digital Transformation and Corporate Governance on Telecommunications Firm Performance in Indonesia (2021–2024) - Sri Supadmini; Imam Subaweh (Invoice : Jurnal Ilmu Akuntansi, 2026)
Digital transformation has become a critical driver of organizational outcomes in technology-intensive industries; however, prior studies have largely emphasized its direct impact on performance without clearly distinguishing between financial performance and firm value as conceptually different constructs. Moreover, limited attention has been given to the role of corporate governance in shaping these relationships, particularly in emerging market contexts. This study aims to examine (1) the effect of digital transformation on financial performance, (2) the effect of corporate governance on financial performance, and (3) the moderating role of corporate governance in the relationship between digital transformation and firm value. This research employs a quantitative explanatory design using panel data regression analysis. The sample comprises three major telecommunications companies listed on the Indonesia Stock Exchange, selected based on data availability and industry relevance, with quarterly observations from 2021 to 2024, resulting in 48 firm-quarter observations. Digital transformation is proxied by IT capital expenditure intensity, corporate governance is measured using a governance disclosure index, financial performance is captured by Return on Assets (ROA), and firm value is measured using Tobin’s Q. Moderation analysis is conducted using an interaction term between digital transformation and corporate governance. The results show that digital transformation significantly improves financial performance, while corporate governance has a positive effect on financial performance. In addition, corporate governance strengthens the positive relationship between digital transformation and firm value, indicating its role as an effective moderating mechanism. These findings confirm that financial performance and firm value represent distinct outcomes of digital transformation, and that governance plays a crucial role in bridging technological investment and market valuation. This study contributes to the literature by clarifying the dual outcomes of digital transformation and highlighting the contingent role of governance in enhancing firm value within the telecommunications sector.